Knowledge, Attitudes, and Beliefs of Parents Toward the Human Papilloma Virus Vaccine - Aylin Kurt; Ebru Cirban Ekrem; Fatma Dinç (Galenos Publishing House, 2024)
Objective: To evaluate the attitudes, beliefs, and knowledge of parents regarding the human papilloma virus (HPV) vaccine. Method: We conducted a cross-sectional study using a digitally prepared survey form delivered via social media platforms to 420 participants with children aged 9-18 years. "Data collection forms included the descriptive information form and health belief model scale on HPV infection and vaccination." Statistical differences between the groups were analyzed using t-tests and ANOVA. The source of the discrepancy among groups (post-hoc) was examined using the Bonferroni test. Results: Among the parents, 53.3% lacked adequate knowledge regarding the vaccine, 92.4% had not vaccinated their children against HPV, and another 39.5% were undecided regarding vaccination. The primary reason for not vaccinating, as reported by 34.0% of respondents, was inadequate knowledge regarding the vaccine. Differences were observed in the perceived benefit, barrier, sensitivity, and severity of HPV vaccines based on hearing about the vaccine, personal vaccination status, consideration of vaccinating one's child, source of vaccine information, fear of vaccine side effects, and lack of information (p<0.05). Conclusion: The study found that most participating parents lacked sufficient knowledge on HPV vaccines. Beliefs about HPV vaccination were affected by fear of side effects, scarcity of information, and seeking information from non-healthcare sources. In future research, it is recommended that healthcare providers, such as nurses, who offer health services to their community and have education and counseling duties related to health, prepare and enact training initiatives on HPV vaccination for both parents and adolescents.